Nutrition and the Risk of Alzheimer's Disease - Sun, Lei; Wang, Ying-Li; Tan, Lin; Yu, Jin-Tai; Hu, Nan; Tan, Lan (BioMed research international, 2013)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder that accounts for the major cause of dementia, and the increasing worldwide prevalence of AD is a major public health concern. Increasing epidemiological studies suggest that diet and nutrition might be important modifiable risk factors for AD. Dietary supplementation of antioxidants, B vitamins, polyphenols, and polyunsaturated fatty acids are beneficial to AD, and consumptions of fish, fruits, vegetables, coffee, and light-to-moderate alcohol reduce the risk of AD. However, many of the results from randomized controlled trials are contradictory to that of epidemiological studies. Dietary patterns summarizing an overall diet are gaining momentum in recent years. Adherence to a healthy diet, the Japanese diet, and the Mediterranean diet is associated with a lower risk of AD. This paper will focus on the evidence linking many nutrients, foods, and dietary patterns to AD.